Prolonging the Lifetime of Wireless Sensor Networks using LPA-star Search Algorithm - Ahmed A. Alkathmawee; Lusong Feng; Imad S. Alshawi (Institute of Advanced Engineering and Science, 2016)
Since sensors have limited power resources, energy consumption has become a critical challenge to Wireless Sensor Networks (WSNs). Most of the routing protocols proposed to transmit data packets through paths which consume low energy aim simply to reduce battery power consumption. This can lead to lead to network partition and reduce network lifetime.Therefore, to balance energy consumption and extend network lifetime while minimizing packet delivery delay; this paper proposes a new energy-routing protocol using the lifelong planning A-star (LPA-star) search algorithm. This algorithm is used to find an optimum forwarding path between the source node and the sink. The optimum path can be selected depending on highest residual sensor energy, the shortest distance to the sink and lowest traffic load. Simulation results indicate that the proposed protocol increased the lifetime of the network compared with the A-star routing (EERP) protocol.